Human capital and open innovation: Do social media networking and knowledge sharing matter? - Lyna Latifah; Doddy Setiawan; Y. Anni Aryani; Isfenti Sadalia; Mohammad Nur Rianto Al Arif (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This study provides empirical evidence of the effect of human capital on innovation in young entrepreneurs' SMEs. Furthermore, this study also examines the role of social media networking and knowledge sharing, as a mediating variable, on the effect of human capital on open innovation. The current study employs the survey method to collect data. The respondents of this study are 438 young entrepreneurs who attended incubators by universities in Central Java and Yogyakarta, Indonesia. Data analysis techniques include using Structural Equation Modeling (SEM) with AMOS software. The result shows that human capital, knowledge sharing, and social media networking directly affect innovation. Social media networking and knowledge sharing partially mediate the effect of human capital on innovation.
Keywords: 650; a young entrepreneur; human capital; innovation; knowledge sharing; social media networking